On the characteristics of pressure wave at mountain stations (MAUSAM, 1972)
Mean hourly pressure data from two mountain stations above 2 km, Kodaikanal and Ooty are analysed using Fourier analysis, The 12-hr wave fits into the pattern discovered by other workers in the field. In contrast, the 24-hr wave shows a phase difference of about 1800 between Kodaikanal and Ooty. A sort of reversal in the diurnal wave around 2.km level is suspected. Harmonic analyses of temperature data in respect of these hill stations did not reveal any significant differences between them.